PENGEMBANGAN MEDIA IT PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Ahmad Faozi; Uli Marfu’ah (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2026)
This Study aims to analyze the development and utilization of informasi technology based learning media in Islamic Religius Education (Pendidikan Agama Islam/PAI) learning and to identify supporthing and inhibiting factors in its implementation. Islamic Regilious Education plys an important role in shaping students’ religious attitudes and understanding of islamic values. This research employed a qualitative approach with data collection techinigues including classrom observation, questionnaires, and library research derived from relevant academic journals and books. The findings indicate that the use of information technology based learning media, such as visual media and interactive multimedia, can increase students’ active participation, enhance their understanding of learning materials, and create a more engaging and contextual learning environment. The utilization of IT-based media also assists teachers in delivering abstract PAI materials more effectively. However, several obstacles were identified, including limited facilities and infrastructure, differences in students’ technological abilities, and limited instructional time. Therefore, continuous development and optimization of information technology based learning media are necessary to improve the quality of Islamic Religious Education learning.